Forced Migration of Rohingya Refugees from Myanmar to Neighboring Countries: A Humanitarian Crisis Unresolved - Fahim, Md. Hasnath Kabir (Society & Sustainability, 2022)
In this current world, the Rohingya Muslims of Myanmar are deemed to be one of the most inhumanly tortured minorities. The culture of racial persecution is indulged by the decades of a clash between the Myanmar Government and the Rohingyas regarding religious and ethnic variance. However, it is also argued that the Rohingya crisis is not confined to religion but comprises economic and political issues equally. Rohingyas have been deprived of their basic human rights and faced a security crisis. Mass killing, rape, and inhuman torture are notable in this regard. Methodical abuse of human rights of the Rohingya by the military junta of Myanmar has forced thousands of Rohingya to flee the country. Consequently, thousands of Rohingyas now reside as refugees, mostly in Bangladesh, while others escaped to Malaysia, Singapore, and the Middle East. The Government of Myanmar has denied the citizenship of Rohingyas and labeled them as foreigners. This paper highlights the measures adopted by the global community for preventing the mass killing of Rohingyas. This research also portrays the means and methods of the Myanmar Government to suppress the Rohingyas. Furthermore, this paper looks into all sorts of violations of human rights and humanitarian disasters suffered by the Rohingyas and the subsequent humanitarian aid received from the regional and international community.